Four-step total synthesis of (+)-yaoshanenolides A and B - Thorat, Sagar S.; Palange, Megha N.; Kontham, Ravindar (ACS Omega, 2018)
A highly concise bioinspired four-step total synthesis of yaoshanenolides A and B possessing tricyclic spirolactone with an unusual 5'H-spiro-[bicyclo[2.2.2]-oct[2] ene-7,2'-furan]-5'-one scaffold is reported. This synthesis features high-yielding aldol-type addition of gamma-butyrolactone on to the aldehyde, exocyclic olefination of lactone derivative using Eschenmoser's salt, and highly facial-and endo-selective [4 + 2]-cycloaddition of fully functionalized 5-methylene-2(5H)-furanone with natural R-(-)-alpha-phellandrene. The approach allows access to yaoshanenolides A and B in four linear steps in 11 and 13% overall yield.

TiCl4-n-Bu3N-mediated cascade annulation of ketones with alpha-ketoesters: a facile synthesis of highly substituted fused gamma-alkylidene-butenolides - Palange, Megha N.; Gonnade, Rajesh G.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2019)
A facile protocol for the synthesis of highly substituted fused gamma-alkylidene butenolides using direct annulation of ketones with alpha-ketoesters, which proceeds through TiCl4-n-Bu3N mediated aldol addition followed by an intramolecular enol-lactonization/cyclization cascade, is reported. Diverse 6-5, 7-5 and 8-5 fused bicyclic gamma-ylidene butenolides and highly substituted monocyclic analogs related to biologically relevant natural products were prepared from readily accessible ketone and alpha-ketoester building blocks. The highly step-economic cascade nature, good substrate scope, easy access to complex products with good to excellent yields, gram-scalability, demonstration of synthetic utility, and unambiguous structural confirmation through X-ray crystallography analyses and analogy are the salient features of this work.